The canonical delicts liable to penal sanctions reserved to the Apostolic See - BOREK, DARIUSZ (Prawo Kanoniczne, 2014)
The article titled The Canonical Delicts Liable to Penal Sanctions Reserved to the Apostolic See analyses the consecutive offences under the penalty of latae sententiae excommunication the remission of which is reserved to the Apostolic See. According to the currently applicable canon law, there are only six delicts liable to latae sententiae excommunication the exemption form which is reserved to the Apostolic See. They are: profanation of consecrated species; physical assault upon the Roman Pontiff; absolution of an accomplice in a sin against the sixth commandment of the Decalogue; consecration of a bishop without a pontifical mandate; direct violation of sacramental seal; an attempt to ordain a woman to the priesthood. The knowledge of essential features of these offences seem particularly important in re-examining the case and resolving whether the penalty of excommunication, reserved to the Apostolic See, has actually been incurred.